2007
DOI: 10.1258/000456307780118163
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of interpretation in clinical biochemistry: a personal view

Abstract: In many laboratories, clinical biochemists add interpretative comments to laboratory reports. There is, however, little evidence base to support this activity. Interpretative comments attached to reports are quite complex, usually consisting of several components that may suggest possible diagnoses and additional tests. Every comment is different, and assessment of interpretation is difficult. We illustrate different approaches which can be used: assessing whole comments or comment components or key phrases; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Most UK laboratories have a Duty Biochemist (a suitably qualified senior medical or scientific professional) who adds interpretative comments on certain biochemistry reports, where the additional comment is considered to 'add value' to the requesting doctor or nurse. These activities have been considered in this journal on many occasions, 1,2 but even today there is little evidence that the activity is effective or appreciated by users of the service.…”
Section: Introductionmentioning
confidence: 99%
“…Most UK laboratories have a Duty Biochemist (a suitably qualified senior medical or scientific professional) who adds interpretative comments on certain biochemistry reports, where the additional comment is considered to 'add value' to the requesting doctor or nurse. These activities have been considered in this journal on many occasions, 1,2 but even today there is little evidence that the activity is effective or appreciated by users of the service.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, even the quality of the interpretation offered by an expert system will be depend-ent on the knowledge and commenting skills of the person building the knowledge base. Proficiency testing of this activity has only recently been attempted (22). Narrative interpretative comments are still a voluntary and unregulated aspect of a laboratory result.…”
mentioning
confidence: 99%
“…There is some evidence that they lead to improved outcomes compared to reports without comments [13]. The quality of interpretive commenting in clinical chemistry has been assessed by proficiency testing schemes and has found that unacceptable interpretation can be made [14][15][16][17] and lead to the conclusion that formal training of pathologists and clinical scientists should be provided [18][19][20], concentrating on how to comment as much as what to comment [21,22].…”
Section: The Post-analytical Phasementioning
confidence: 99%